2024
DOI: 10.1021/acs.jnatprod.3c01040
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review of Patented Antimicrobial Peptides from Amphibian Anurans

Fabiola Almeida García,
Talia Frómeta Fuentes,
Isel Pascual Alonso
et al.

Abstract: Since the 1980s, studies of antimicrobial peptides (AMPs) derived from anuran skin secretions have unveiled remarkable structural diversity and a wide range of activities. This study explores the potential of these peptides for drug development by examining granted patents, amino acid modifications related to patented peptides, and recent amphibians' taxonomic updates influencing AMP names. A total of 188 granted patents related to different anuran peptides were found, with Asia and North America being the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 119 publications
(285 reference statements)
0
3
0
Order By: Relevance
“…AMPs from anurans have been studied for the last four decades, and interest in them has increased with the global health emergency of antimicrobial resistance. It has been shown that anuran AMPs are targets of patents that propose their development as new drugs, including through bioengineering involving amino acid modifications [20]. In this…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AMPs from anurans have been studied for the last four decades, and interest in them has increased with the global health emergency of antimicrobial resistance. It has been shown that anuran AMPs are targets of patents that propose their development as new drugs, including through bioengineering involving amino acid modifications [20]. In this…”
Section: Discussionmentioning
confidence: 99%
“…AMPs from anurans have been studied for the last four decades, and interest in them has increased with the global health emergency of antimicrobial resistance. It has been shown that anuran AMPs are targets of patents that propose their development as new drugs, including through bioengineering involving amino acid modifications [20]. In this work, we performed the fractionation of skin secretion from L. vastus (LSV) from the Brazilian northeast and ended up isolating a new peptide belonging to the group of ocellatins.…”
Section: Discussionmentioning
confidence: 99%
“…Since the pioneering studies by the Erspamer group, it has been well-established that anuran skin secretion harbors a diverse array of compounds, exhibiting a wide spectrum of biological activity. Among these compounds are host defense peptides (HDPs), known for their capability to inhibit bacterial growth and demonstrating remarkable diversity in their bioactivity spectrum against a wide range of microorganisms. These molecules hold significant potential for drug development. , …”
mentioning
confidence: 99%